Time Matters: A Swedish Cohort Study of Labor Duration and Risk of Uterine Rupture. Issue 3 (24th September 2022) - Hesselman, S.; Lampa, E.; Wikman, A.; Törn, A.E.; Högberg, U.L.f.; Wikström, A.-K.; Jonsson, M.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100:1902–1909) In medium- to high-resource settings, a previous cesarean delivery (CD) is the main risk factor for uterine rupture, which is associated with maternal and neonatal morbidity and mortality. Induction of labor and augmentation of labor with oxytocin are both modifiable risk factors but are also common in patients who do not experience uterine rupture. One risk factor that could potentially help identify patients at risk of uterine rupture is slower progression in labor. This study aimed to examine the relationship between duration of labor and uterine rupture in the first trial of labor after one CD. The study also aimed to evaluate risk factors such as induction and use of prostaglandins, oxytocin, and epidural analgesia.